Does the community service environment affect the willingness of older adults people to socialize for older adults care? - Huang, Denghui; Feng, Ran; Shi, Minxuan (Frontiers in Public Health, 2024)
Population ageing is a significant trend in social development and will remain a fundamental national condition in China for the foreseeable future. Socialized elderly care has become a crucial strategy for China to address population ageing. However, the current levels of acceptance and willingness to seek socialized elderly care among older adults are relatively low. This study focuses on examining how the community environment and services influence elderly people's willingness to engage in social activities related to elderly care. Using data from the China Longitudinal Aging Social Survey (CLASS) (N=9657), this study investigated the impact of the community service environment on elderly people's willingness to participate in social activities related to elderly care through a logit model. The study revealed that 9.15% of older adults (N=9657) in China are willing to engage in social activities related to elderly care. Furthermore, the individual characteristics and family support of older adults play a significant role in shaping their willingness to engage in elderly care. The provision of medical services, daily care services, and entertainment venues by the community positively influence elderly people's willingness to participate in social activities related to elderly care (p<0.01), whereas psychological counselling services have a negative impact (p<0.01). The impact of community services on elderly people's willingness to engage in social activities related to elderly care varies due to factors such as smoking and chronic diseases. These findings provide valuable insights for improving older adults' social engagement in China.